Actitudes en la prevención de riesgos laborales en trabajadores de construcción civil del consorcio San Antonio. 2023 - Tello Oroche, Kathia Lizbeth (2023)
The objective of this research work was to study the attitudes towards the prevention of occupational accidents in civil construction workers in San Antonio in the year 2023. The research, due to its approach, was quantitative, prospective, of a simple descriptive level and of design of non-experimental research. The target population of the study was made up of 183 workers (183) of the San Antonio consortium who were working in the year 2023. The sample was also made up of 79 workers who were present at the time of application of the data collection instrument. , inclusion and exclusion criteria were taken into account, the technique used was the survey and the instrument applied was the questionnaire of ten positive and negative statements, which passed the validity tests (Aiken valides index) and reliability (Crombach’s alpha test). The data obtained through the data collection instrument was analyzed taking into account the objectives and research hypothesis and subsequently expressed in a Basic Data Matrix (MBD) and analyzed, processed and tabulated through of the SPSS statistical package version 27. The main results expressed that there are mostly favorable and very favorable general attitudes towards the prevention of occupational accidents in civil construction workers belonging to the San Antonio consortium in the year 2023. This predominance is also manifested according to age groups as well as according to the worker’s level of education. This tendency is also expressed in cognitive, affective and reactive attitudes and according to the age group and level of education. There is an important group of workers with neutral attitudes towards the prevention of occupational accidents within the age groups and level of education. Therefore, it is necessary to strengthen the importance of preventing occupational accidents, especially in those workers with neutral attitudes in the San Antonio 2023 consortium company.